2004
DOI: 10.1016/j.cardiores.2004.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of polymer-based, slow-release, sirolimus-eluting stents in a porcine coronary model

Abstract: SRL-eluting stents favorably modulate neointimal formation for 30 days in the porcine coronary model. Long-term inhibition of neointimal hyperplasia is not sustained presumably due to delayed cellular proliferation despite increased levels of the cyclin-dependent kinase p27(kip1) in the vessel wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
153
2
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(168 citation statements)
references
References 14 publications
8
153
2
3
Order By: Relevance
“…Thus, we presume the second generation DES should also confront the old problem of delayed neointimal hyperplasia that has been reported in previous brachytherapy 15) and permanent polymer-coated DES studies. 16) Altogether randomized clinical trials with longer term observation are necessary to document a sustained benefit for these novel drug-eluting stents.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we presume the second generation DES should also confront the old problem of delayed neointimal hyperplasia that has been reported in previous brachytherapy 15) and permanent polymer-coated DES studies. 16) Altogether randomized clinical trials with longer term observation are necessary to document a sustained benefit for these novel drug-eluting stents.…”
Section: Discussionmentioning
confidence: 99%
“…However, DES have been associated with a higher frequency of very late stenosis and re-infarction (more than 1 year) compared with bare metal stents, 1.9% versus 0.6% per year, respectively. 1,2 In addition, animal studies have shown that DES can cause local toxicity to the vessel wall in the form of medial necrosis, intimal proliferation, chronic inflammation and delayed re-endothelialization of the stents. [1][2][3] Thus, although DES reduce the risk of restenosis, they are associated with delayed re-endothelialization.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition, animal studies have shown that DES can cause local toxicity to the vessel wall in the form of medial necrosis, intimal proliferation, chronic inflammation and delayed re-endothelialization of the stents. [1][2][3] Thus, although DES reduce the risk of restenosis, they are associated with delayed re-endothelialization. 4,5 An optimal therapeutic approach would involve a strategy, which inhibits intimal hyperplasia while promoting re-endothelialization and suppressing stent-or vector-related inflammatory side effects.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon repeated itself with brachytherapy. No long-term benefit was seen in animal models but humans did benefit [263,[265][266][267][268][269]. Serruys et al state: "Finally, because the results of experiments in animal models cannot be directly translated to humans, specific clinical trials of safety and efficacy are required for each device [DES] [270].…”
Section: Palmaz Et Al First Employed Stents In Peripheral Arteries Imentioning
confidence: 99%